(untitled) (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
The problem of early marriage in Banyuwangi Regency is still very serious and causes a high risk of divorce. This study intends to analyze the factors of underage marriage and its relationship with divorce rates. It employs empirical legal research method with qualitative approach. Data were collected through interviews, observations and documentation at the Banyuwangi Religious Court, involving judges, clerks and relevant informants of early marriage and divorce cases. The findings show that there are a number of factors that affect early marriage which include; avoiding adultery, low economic condition, socio-cultural pressure and premarital pregnancy. The main causes of divorce include economic hardship, ongoing conflict, abandonment and domestic violence. Although early marriage is not a direct cause of divorce, it is strongly associated with instability in marriage, especially due to the lack of emotional, mental and financial readiness of young couples. The study concluded that early marriage increases the risk of divorce when couples are not ready for marriage life. Therefore, it is essential to increase public awareness, promote education on appropriate ages of marriage, and strengthen institutional roles in guidance for the establishment of stable and harmonious families.